Elaboración de un sistema digital para la guia de archivos existentes en el sistema educativo intercultural cotopaxi del colegio intercultural bilingüe jatari unancha durante el periodo 2014-2015 - Chicaiza Quishpe, Cristina Karolina (2015)
The research was done in the secretary of the Cotopaxi Intercultural Education System, “Jatari Unancha” Intercultural Bilingual School, It had the collaboration of the 5 members of the secretarial department of the institution. The main objective of the study is the order of the physical file and the development of a digital archiving facilitating the records management and the attention of the secretarial department to the students of first and second of BGU, because the file records for high school students are manipulated throughout the school year and there is a strong possibility that loss or spoilage by handling and not knowing exactly where the file is required given the need for the development….